ANALYSIS OF THE ROLE OF SCHOOL ENVIRONMENT IN ENHANCING SELF-CONFIDENCE OF 4TH-GRADE STUDENTS AT SDIT AT-TAQWA - Muslimah, Revi; Riyadi, Arie Rakhmat; Giwangsa, Sendi Fauzi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
This research examines the impact of the school environment on the self-confidence of 4th-grade students at SDIT At-Taqwa. Using a qualitative case study approach, it explores social dynamics within elementary education. Data were collected through participatory observation and in-depth interviews with the principal, homeroom teachers, subject teachers, and students. Documentation reviewed included activity photographs, school records, and program archives. Data analysis followed Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing. Results indicate that the school’s social environment substantially enhances self-confidence, with 82% of students exhibiting improvement. Contributing factors include positive teacher feedback, practical homeroom guidance, strong peer relationships, and structured programs such as Ta’lim that foster public-speaking skills. Supportive physical spaces, interactive classrooms, and participatory curricula further contribute to this development. Students engaged in extracurricular activities and competitions show marked growth. The findings suggest that a supportive and well-structured school environment fosters self-confidence and offers practical guidance for collaborative character-building initiatives. Future research should explore the influence of the school environment on additional character traits, including leadership, responsibility, empathy, and communication skills.